Evaluating the face and content validity of an instructional technology competency instrument for university lecturers in Malaysia - Lam, Kim Wai; Hassan, Aminuddin; Sulaiman, Tajularipin; Kamarudin, Nurzatulshima (Human Resource Management Academic Research Society, 2018)
The purpose of this study was to evaluate the face and content validity of an instrument that had been developed to assess the relevance and comprehensiveness of instructional technology competencies as perceived by Malaysian university lecturers. The face validity and content validity of the instrument was investigated based on the opinions of experts. The item content validity index (I-CVI) and scale content validity index (S-CVI) were calculated by adopting the mean approach and inter-rater agreement. The scale was revised based on comments from a panel of three experts in the qualitative review stage, and thereafter, evaluated by another group of five experts in the quantitative review stage. The findings at the face validity stage yielded 8 domains with 71 items being retained, based on 75 percent or more agreement from expert responses. The content validity of the instrument was assessed by S-CVI/UA and S-CVI/Ave, yielding scores of .81 and .90 respectively. Findings indicated that this instrument had excellent face and content validity and could thus be used to assess the relevance and comprehensiveness of instructional technology competencies as perceived by Malaysian university lecturers.